OP0286 Effects of an Educational Program on the Safety Knowledge and Skills of Patients with Rheumatoid Arthritis Treated by Biologics. (23rd January 2014) - Pfeffer, L.; Janoly-Dumenil, A.; Donjon, A.; Ouagne, V.; Tebib, J. G.; Piperno, M.
Abstract : Background: Biologics are very efficient drugs used in rheumatoid arthritis (RA) but they are also known for entailing specific risks. Therefore, it is necessary to translate the patients' skills of safety and what decisions to take in some situations. This aspect is developed during the educational program (EP) proposed to patients. Objectives: The aim of this study was to assess the effect of the EP on the safety knowledge and skills of patients treated by biologics. Methods: This study was conduced from September 2010 to December 2012 in the department of rheumatology. The EP consisted in a one-day group session (from 3 to 5 patients affected by RA), which took place after individual sessions (these ones aimed at identifying the patients' educational needs). The main educational sessions themes were: the disease and medications, joint protection during usual daily-life activities, self-learning exercises in order to perform at home, suggestions about the way to adapt the surrounding environment. Besides, some additional individual sessions were proposed to patients if needed. Moreover, a long term monitoring was realised for each patient (face-to-face or phone call interviews after 1, 3 and 6 months). The safety competences were assessed thanks to the validated BioSECURE questionnaire (score from 0 to 100) that includes how to deal with infections and other adverse events which may occur while having a biologic, but also, how to prevent and avoid them. The questionnaire is composed by 55 questions and can be used for all of the current available biologic drugs. It is also easy to fill in (approximately 10 minutes) and has some good psychometric properties. Two conditions were necessary for patients to be part of the EP: they were treated by biotherapy and they had completed at least two questionnaires. The scores were measured before the EP beginning (at M0) and 1 (M1), then 3 (M3) and 6 (M6) months after the EP group session had taken place. The scores were analysed at these different stages of the process by the ANOVA test. Results: Forty-three patients were included in the study (5 males and 38 females). The average age was 60 years old, (min 33, max 82). The patients' mean disease duration (±sd ) was 13 ± 11 years and the mean biologics treatment duration (±sd ) was 26 ± 25 months. Fifty-one percent of the patients had fully completed the SECURE questionnaires (M0, M1, M3 and M6), 37% had completed it three times and 12% two times. The average scores (±sd) were respectively 64, 4 (± 11, 8), 82, 9 (± 9, 6), 87, 7 (± 8, 3) and 93, 3 (± 5, 2) at M0 (n =43), M1 (n =34), M3 (n =34) and M6 (n =34) respectively. The improvement of the scores was statistically significant (p<0, 0001). Conclusions: These results show the positive effect of the EP on safety knowledge and skills in patients treated by biologics. The BioSECURE score continues to increase 6 months after the EP session. This result could be explained by the close monitoring realised by the EP team that fits into the continuous process related to the patients' understanding and needs. For some items of the questionnaire the patients' answers are inadequate, even after the EP. This has to be taken into consideration in the perspective of improving the contains of the next EP sessions. Disclosure of Interest: None Declared